Meningkatkan Daya Saing Destinasi Pulau Rakit: Strategi Penetapan Harga Tiket Kapal yang Efektif - Rini Indarti; Imam Sutrisno; Iskandar (Bulletin of Community Engagement, 2024)
This research aims to optimize ship ticket pricing as a strategy to increase the competitiveness of the Rakit Island tourist destination. Through quantitative and qualitative approaches, this research analyzes the factors that influence the decision to purchase ship tickets as well as the elasticity of demand to price changes. The research method includes collecting primary data through surveys of tourists and secondary data related to the number of tourist visits and market characteristics. The research results show that boat ticket prices have a significant influence on tourists' decisions to visit Rakit Island. Apart from that, other factors such as service quality, tourism facilities and promotions also play an important role. Based on these findings, this research provides recommendations regarding optimal boat ticket pricing strategies to increase the competitiveness of Rakit Island and maximize income from the tourism sector